MICROSOFT VISUAL BASIC 6.0 APPLICATION TO LOOK FOR MULTIPLES OF THE SMALLEST AND THE FELLOWSHIP OF THE BIGGEST FACTORS FOR CHILDREN - Muhammad Nur; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2003)
Least Earned search Guild (KPK) and the Fellowship of the Biggest Factors (GCF) in math has always considered it a dizzying, especially for children. Therefore, with this application will be able to help facilitate the search for the commission and the GCF by giving a bit of multimedia elements that can be interesting for the kids in the study of this Commission and the GCF. In making the application, use Microsoft Software Visual Basic 6.0.